TATA KELEMBAGAAN DAN NOMENKLATUR ISTIMEWA DAERAH ISTIMEWA YOGYAKARTA: Array - Muchamad Zaenuri; Muhammad Iqbal; Yunita Elianda (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
Yogyakarta Special Region (DIY) is an area that has a unique government structure called special. Its specialty is also found in the different governmental institutional regulations from other regions. In this case this feature can be seen in the formation of institutions in the Yogyakarta Istemewa Region which have special duties in accordance with the task of regulating privileges. Descriptive qualitative research methods. The results of this study are the features that exist in the regional government system in DI Yogyakarta, namely, in the special institutions of Yogyakarta there are four institutions, namely Parampara Praja, Paniradya Ka Privileges, Kudha Kabudayan (Cultural Service) and Kundha Niti Mandala Sarta Tata Sasana (Department of Land and Spatial Planning). Name changes not only in the Dinas department but also in the sub-districts and kelurahan in the Regency / City have also experienced this name change. For sub-districts there is a difference in the names of the sub-districts in the city which are named Kemantren while the sub-districts in the Regency are named Kapanewon. Some of the names of the existing structures in the sub-district also changed, such as the camat to become Mantri Pamong Praja, the sub-district secretary to be Mantri Anom, and others. Meanwhile, the Kelurahan becomes the Kalurahan, which is directly below Kapanewon. However, the name change does not change the actual task and function.